Pengaruh Sakti, Kompetensi SDM, dan Penerapan Good Governance Terhadap Kualitas Informasi Laporan Keuangan - Rahmat, Rahmat; Maulina, Rina (Innovative: Journal Of Social Science Research, 2024)
The purpose of this research was to analyze how the following factors—SAKTI, Human Resources Competence, and the Implementation of Good Governance influence the accuracy of financial report data. Participants include all staff members of the National Treasury Service Office (KPPN) Meulaboh unit accountable for financial management. The research sample of 31 participants was chosen using a non-probability sampling technique called the saturated sampling method. By sending out surveys to people, we were able to collect primary data. Using SPSS 23 as a data analysis tool, the multiple linear regression method was employed. Partial testing results show that SAKTI and the Implementation of Good Governance cannot be considered independent variables influencing the quality of financial report information. However, it has been demonstrated that Human Resources Competence significantly impacts the accuracy of financial report data. The quality of financial report information is influenced by the variables SAKTI, Human Resources Competence, and the Implementation of Good Governance, according to data from simultaneous testing. Finally, this study sheds light on the KPPN Meulaboh environment and the elements that affect the quality of government financial reports.